Tree-based model for diffuse-type gastric cancer prognostication: a population study based on the Surveillance, Epidemiology, and End Results database - Cai, Lei; Sun, Yeqi; Lv, Beibei; Su, Wenjing; Li, Jia (Translational Cancer Research; Vol 15, No 4 (April 30, 2026): Translational Cancer Research, 2026)
Diffuse-type gastric cancer (DGC), a subtype of the Lauren classification, is characterized by poor differentiation and a poor prognosis, and effective therapeutic options remain limited. This study aimed to explore the prognostic risk stratification of DGC and to evaluate the effects of various clinical factors on prognosis.